Análisis y generalización del material en la investigación sociológica (2010)
ABSTRACT: One of the main characteristic of the development of modern social science is the mathematization of all the branches of the knowledge, especially the penetration of the methods quantitative in the social research. One of the methods related to the penetration in the social investigation of the quantitative methods and to the analysis and interpretation of the data, scales of measurement of attitudes are it (Likert, Thurston, Guttman, etc.). The adoption of the quantitative methods has its origin in: First of all, the compilation of sociological information. One of the fundamental tasks of the investigation continues being the problem of the representative character of the collected material. Second via of penetration of the mathematical one it is the sphere of the data analysis: The preparation of scales of measurement of attitudes is means of analysis of the massive statistical material.